Nurturing humanism and professionalism in a clinical setting: A multicenter study to develop a framework for a learning module for clinical students. - Rita Mustika; Anyta Pinasthika; Nadia Greviana; Eti Poncorini Pamungkasari; Annang Giri Moelyo; Rahma Tsania Zhuhra (PLoS ONE)
Introduction Professionalism represents a contract between physicians and society, with humanism at its core. Humanism must be developed in medical education, especially in clinical settings, as students meet real-life professional situations. However, dynamic and unpredictable clinical settings might expose students to authentic yet unexpected far-from-ideal situations that might hinder the humanism and professionalism process. Furthermore, culture plays an influential role, highlighting the importance of developing an appropriate and contextual learning strategy. Hence, this study aims to conceptualize strategies to teach humanism and professionalism in high-power distance and collectivistic settings. Methods This multicenter qualitative phenomenological study used maximum variation sampling to recruit participants, consisting of clinical students, teachers, and coordinators from three medical schools in Indonesia. Data were collected through focus group discussions (FGDs) and in-depth interviews. Thematic analysis was conducted using the steps of coding and theorization methods. Results A total of 15 FGDs and one in-depth interview were conducted with 57 students, 39 teachers, and 18 coordinators. Socialization theory was used to analyze themes, leading to a culturally related approach to learning. Professional identity formation (PIF) was highlighted as the center of learning humanism and professionalism, with character building as the main principle. Designing a curriculum for humanism and professionalism for clinical learning should consider the longitudinal nature of PIF and ensure that professionalism explicitly exists in the curricula. As cultural impact might pose challenges, it must also be acknowledged and addressed. Meaningful integrated learning experiences, patient exposure, and reflection serve as the cornerstones of teaching-learning strategies while considering longitudinally explicit assessments. Conclusion Nurturing humanism and professionalism in undergraduate clinical settings is a longitudinal character-building process, with PIF as its center. Longitudinal, explicit, and dynamic strategies should be considered as part of the framework of teaching-learning and assessment of humanism and professionalism, as well as faculty development efforts with close attention to cultural factors.